A TAXONOMIC REVISION OF THE GENUS SELAGINELLA (SELAGINELLACEAE: LYCOPODIOPSIDA) FROM PAKISTAN - M. Irfan; G. Jan; F. G. Jan; W. Murad (Journal of Animal and Plant Sciences, 2020)
The current paper represents taxonomic studies of genus Selaginella from Pakistan based upon the studying of plant specimens in different herbaria of Asia, Europe and North America. A total of six species viz. Selaginella aitchisonii Hieron.,Selaginella chrysocaulos (Hook. & Grev.) Spring, Selaginella jacquemontii Spring,Selaginella reticulata (Hook. & Grev.) Spring,Selaginella subdiaphana (Wall. ex Hook. & Grev.) Spring and Selaginella vaginata Spring were reported; detailed descriptions of species, distribution pattern, ecology, general distribution and specimens examined from Pakistan were documented.
Keywords: Flora; Lycophytes; Selaginella; Pakistan; Western Himalaya